Double discharges in human soleus muscle - Piotrkiewicz, Maria; Sebik, Oğuz; Binboğa, Erdal; Młoźniak, Dariusz; Kuraszkiewicz, Bożenna; Türker, Kemal S. (Frontiers in Human Neuroscience, 2013)
Double discharges (doublets) were recorded from human soleus, where they have never been found before. The data analyzed in this study were collected from 12 healthy volunteers. The subjects were recruited for other studies, concerning: (1) estimation of motoneurons’ afterhyperpolarization duration and (2) analysis of motor unit responses to nerve stimulation, and were not trained to voluntarily evoke doublets. The majority of doublet intervals fell into the commonly accepted range 2–20 ms. However, two soleus motoneurons from one subject presented exceptional doublets of interval about 37 ms. This interval was virtually identical with the interval between second and third discharge in the few triplets recorded from another subject. It is hypothesized that triplets are generated by the delayed depolarization with the second narrow hump, which is the same as the hump responsible for exceptional doublets.